Scaling up computational thinking skills in computer-assisted language learning (CTsCALL) and its fitness with language learners’ intentions to use virtual exchange: A bi-symmetric approach - Amir Reza Rahimi; Ana Sevilla-Pavón (Computers in Human Behavior Reports)
Many studies have demonstrated that Virtual Exchange (VE) for teaching languages can have a positive effect on learners' intercultural awareness or achievements. However, during this century, the teaching process has shifted from teaching with technology to solving problems with it. In this regard, pedagogical experts in Science, Technology, Engineering, and Mathematics (STEM) have developed programming and robotics based on Computational Thinking skills (CTs), which have been regarded as the core of 21st-century skills. In the field of CALL, this skill has received very little attention. Accordingly, we have attempted to switch the process and outcome of language learning in VE. Thus, we developed the conceptual framework that integrated CTsCALL and Individual-technology-task-environment Fit (ITTEF). Having designed our VE tasks based on CTsCALL, we provided the opportunity for 92 Spanish language learners in our project to exchange language and culture with Cypriot and Irish students and solve VE tasks based on CTsCALL. The result of the symmetric phase of the study validated the five-dimensional structure of CTsCALL and the four-dimensional structures of ITTEF in VE and CALL. It also revealed that language learners, who focused on the key information rather than the details while solving language tasks, as well as recognizing the pattern of task solving and applying them to other tasks, found VE, and CTsCALL to be aligned with their current capabilities, learning environment, and problem-solving skills that mediated their intention to learn and exchange information in this context in the future. Furthermore, the asymmetrical part of the study revealed that sixteen solutions are available to shape language learners' continued intention to use VE by combining the components of CTsCALL and ITTEF. Thus, the study developed the CTsCALL questionnaire and its theory into CALL together with the Council of Europe's Common European Framework of Reference for Languages and recommended that CALL researchers and educators take a broader view of VE, as well as continuing to validate CTsCALL in other CALL disciplines to show that this skill belongs to CALL as well.